Relationship between unemployment rate and shadow economy of selected mena countries: a toda -yamamoto and panel causality approach - Rizgar Abdlkarim Abdlaziz; Faisal Ali Khurshid; Hatem Hatef Abdulkadhim Altaee (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
This research is an attempt to investigate the causal relationship between the shadow economy and unemployment rate for selected Middle East and North African countries. The Toda -Yamamoto causality approach and panel Granger causality test are applied. The Toda -Yamamoto results reveal bidirectional causality for Algeria only. However, unidirectional causality running from unemployment to shadow economy found for Turkey and Qatar, the vice versa for Bahrain, Jordan, and Lebanon. Moreover, the panel Granger causality results show bidirectional causality for the MENA region when one and three lags are used. Nevertheless, unidirectional causality running from the shadow economy to the unemployment rate is found when two, four, and five lags are used.